2019
DOI: 10.1002/jsfa.9984
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin administration post‐weaning attenuates high‐fructose, high‐cholesterol diet‐induced hepatic steatosis in growing, female, Sprague Dawley rat pups

Abstract: BACKGROUND Fructose and cholesterol‐rich diets have been implicated in the upsurge of metabolic syndrome (MetS). Phytochemicals are being explored as alternatives for the prevention and management of MetS. Thirty‐six 21‐day‐old, female Sprague Dawley rats fed a high‐fructose, high‐cholesterol diet post‐weaning were used to investigate the prophylactic potential of quercetin. Group 1 was given standard rat chow (SRC); Group 2: SRC and quercetin (75 mg kg−1 daily); Group 3: SRC and fenofibrate (100 mg kg−1 daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…26,27 In animal studies, it has also been confirmed that 20% fructose exposure can lead to lipid metabolism disorders by stimulating triglyceride and free fatty acid synthesis. 28,29 In this study, consistent with previous studies, 30,31 the increased body weight, serum lipid level, and hepatic lipid accumulation of the FRU group suggested that 20% fructose feeding for 10 weeks induced lipid metabolism disorder.…”
Section: Discussionsupporting
confidence: 91%
“…26,27 In animal studies, it has also been confirmed that 20% fructose exposure can lead to lipid metabolism disorders by stimulating triglyceride and free fatty acid synthesis. 28,29 In this study, consistent with previous studies, 30,31 the increased body weight, serum lipid level, and hepatic lipid accumulation of the FRU group suggested that 20% fructose feeding for 10 weeks induced lipid metabolism disorder.…”
Section: Discussionsupporting
confidence: 91%
“…NAFLD refers to the presence of greater than 5–10% lipid content accumulation in the liver, which eventually leads to increased oxidative stress within the hepatocytes, reduced oxidation of fatty acids, and increased triglyceride synthesis and accumulation. [ 45 ]…”
Section: Pathophysiology Of Nafldmentioning
confidence: 99%
“…The animal experiments of Xin et al and the mass spectrometry analysis Du et al showed that both the enterohepatic circulation and the intestinal flora are involved in the absorption process of quercetin and kaempferol and that isorhamnetin 3-O-glucoside could be successively decomposed into quercetin and kaempferol under bacterial action ( Du et al, 2014 ; Du et al, 2017 ; Xin et al, 2019 ). A number of animal experiments have shown that quercetin can improve hepatic steatosis and prevent hepatic lipid accumulation, thereby treating NAFL ( Esrefoglu et al, 2017 ; Donaldson et al, 2019 ). Therefore, we believe that HRG may improve intestinal inflammation, intestinal immunity, and lipid synthesis through relevant pathways, thereby improving NAFL by regulating intestinal flora.…”
Section: Discussionmentioning
confidence: 99%